The Tekenu and Ancient Egyptian Funerary Ritual - West, Glennise, (Archaeopress Egyptology ;, 2019)
What is the 'Tekenu'? What was its function? What are its origins? These are questions upon which Egyptologists have long pondered but have not, until now, produced any major work to provide answers. Previous treatments of the 'Tekenu' largely adopt a selective approach focusing on a specific form. Rarely has the 'Tekenu' been examined profoundly in all its forms or contexts and its possible origins have been commented upon merely in passing. The aim of this book is to provide a provocative examination and interpretation of the 'Tekenu' in an endeavour to proffer plausible answers hitherto eluding scholars. Attested from the Fifth Dynasty until, and including, the Saite Period, the 'Tekenu' is a puzzling icon which is depicted within the funerary scenes in the tombs of some ancient Egyptian nobles. In this work four distinct types of 'Tekenu' are identified and classified and then a Corpus Catalogue is formed. This book will be of interest to the serious student as well as to anyone fascinated by the hidden messages to be revealed in the funerary iconography of ancient Egyptian tombs.